Legal Implications of Illegal Cigarette Circulation on State Revenue - Rino Dedi Aringga (Ipso Jure, 2025)
The circulation of illegal cigarettes in Indonesia is a serious problem that affects various aspects, including the economy, law, and public health. Illegal cigarettes, whether in the form of no excise stamps, counterfeit excise stamps, or the use of used excise stamps, have caused significant leakage of state revenue. Based on data from the Directorate General of Customs and Excise (DGCE), the circulation of illegal cigarettes ranges from 4-7% of total national consumption, contributing to the loss of trillions of rupiah in excise revenue each year. This implies a reduction in the budget that should be used to finance health services and infrastructure development. In addition, the circulation of illegal cigarettes creates unfair competition for the legal cigarette industry, which faces pressure due to high excise tax rates and decreased market competitiveness. This research uses a normative juridical method with statutory, conceptual and case approaches to analyze the effectiveness of existing regulations, especially in the context of Law No. 39/2007 on Excise. The results show that weak supervision and law enforcement, coupled with corrupt practices in several distribution channels, have made existing policies ineffective in suppressing the circulation of illegal cigarettes. Therefore, it is necessary to strengthen coordination between law enforcement officials, DGCE, and the application of digital technology in the excise control system in order to increase the effectiveness of controlling illegal cigarettes and maximize state revenue